The Influence of Training on Work Ethic of MSME Actors in Pesisir Selatan Regency - Febrila, Tyara; Eriyanti, Fitri (The Future of Education Journal, 2025)
Low work ethic is the basis for this research Small and Medium Industry (SMI) business actors in the Pesisir Selatan Regency area, an area that has a wealth of fishery potential but still needs improvement in the aspect of developing human resource capabilities. The government and related institutions have made various efforts to improve their work ethic, one of the steps is by giving continuous training with the aim of improving quality and productivity of business actors. The main objective of this study is to analyze in depth the effect of training on the work ethic of SMEs in Pesisir Selatan Regency. The dependent variable used in this study is work ethic (Y), while training acts as an independent variable. (X). The research sample consisted of 45 fisheries SMI actors who had participated in the training program. The research methodology The research method used is quantitative method, where the data collection uses questionnaire instruments that have gone through validity and reliability testing. To analyze the data, researchers applied simple linear regression techniques using SPSS 23 software to process and interpret the data. This allows researchers to statistically test the causal relationship between training and work ethic. Based on the results of the analysis, there is a positive and significant effect of training on work ethic of SMEs in Pesisir Selatan Regency, where a significance value of 0.000 is obtained which is below 0.05 with a calculated T value of 4.796> T table value 0.68024.